Dynamic Characteristic of CST Gear Transmission System Under Varying Load Working Condition - Chang Hao; Lü Kaibo; Lian Zisheng; Cui Hongwei; Hu Xiaohe (Jixie chuandong)
In order to analyze the dynamic characteristics of gear transmission system in the controlled starting transmission（ CST）,taking the heavy scraper conveyor under varying load working condition as example,a virtual prototype of the system is established and dynamics simulation is carried out,the dynamic meshing force of gears,vibration response of planetary gear and dynamic loads of each bear point are obtained. The simulation results demonstrate that dynamic changes of gear meshing forces can match up with actual gear transmission,the dynamic response of planetary gear reflect the vibration situation of system,the dynamic loads of bear point are affected by the meshing force,the dynamic changes are same. The experiment of CST under varying load working condition is carried out,the test data of meshing frequency is close to the results of simulation which is validated the accuracy of the virtual prototype,besides,the results provide the theory basis for the dynamic performance optimization of CST gear transmission.